If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7p + 4 = -1p + 9 + 2 + 3p Reorder the terms: 4 + 7p = -1p + 9 + 2 + 3p Reorder the terms: 4 + 7p = 9 + 2 + -1p + 3p Combine like terms: 9 + 2 = 11 4 + 7p = 11 + -1p + 3p Combine like terms: -1p + 3p = 2p 4 + 7p = 11 + 2p Solving 4 + 7p = 11 + 2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2p' to each side of the equation. 4 + 7p + -2p = 11 + 2p + -2p Combine like terms: 7p + -2p = 5p 4 + 5p = 11 + 2p + -2p Combine like terms: 2p + -2p = 0 4 + 5p = 11 + 0 4 + 5p = 11 Add '-4' to each side of the equation. 4 + -4 + 5p = 11 + -4 Combine like terms: 4 + -4 = 0 0 + 5p = 11 + -4 5p = 11 + -4 Combine like terms: 11 + -4 = 7 5p = 7 Divide each side by '5'. p = 1.4 Simplifying p = 1.4
| 1/2x-4=17 | | 8-2y+2y+3=3 | | 4y=2(2+12) | | 5(k+5)=-7 | | 4x^5-x^3-240=0 | | 3.52=2.552-4.25+6.25 | | .2847x+30000000=x | | -8=1(-9t+27) | | 4X+10+175-2x=180 | | -8=1(-9+27) | | 1.2x^2+.4x=.50 | | (64n^12)^-1/6 | | 4x=1/1024 | | 4x=3(x+3)+4 | | 8t-40=12t+30-10 | | 2z-2=-14+6z | | 6t-14=13+9t | | 2(3+4x)-5=25 | | 3x-23=2x-14 | | 3x+4=4(X-3) | | 5/9=10/x | | .25x+20=50 | | 3y^2-y=equation | | 3y^2-y= | | 12x^4-60x^2-432=0 | | 120=10x+10 | | 1/3b-25 | | 65x=110x | | 12x+y=59 | | 10+7x=21-4x | | 11-5x=2-7x | | (3x/2)-x=(x/6)-(4/3) |